2009
DOI: 10.1007/s11064-009-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial Respiratory Chain in the Brain of Adult Rats After Acute and Chronic Administration of Methylphenidate

Abstract: Methylphenidate (MPH) is frequently prescribed for the treatment of attention deficit/hyperactivity disorder. It was previously demonstrated that MPH altered brain metabolic activity. Most cell energy is obtained through oxidative phosphorylation, in the mitochondrial respiratory chain. However, there are still few studies about MPH effects on the brain of adult rats. Thus, in the present study we evaluated the effect of acute or chronic administration of MPH on the activities of mitochondrial respiratory chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Türkbay et al (2009 reported that chronic administration of methylphenidate induces lipid peroxidation in the young rats' striatum. In two different studies conducted by Fagundes et al (2007Fagundes et al ( , 2010, it has been shown that chronic methylphenidate exposure affected different activities in the brains of young and adult rats-while increasing mitochondrial respiratory chain enzymes in young rats' brains, it reduced them in adult brains. Andreazza et al (2007) has shown that methylphenidate led to central (in cells of the striatum and hippocampus tıssues of the brain) and peripheral (blood leukocytes) early DNA damage in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Türkbay et al (2009 reported that chronic administration of methylphenidate induces lipid peroxidation in the young rats' striatum. In two different studies conducted by Fagundes et al (2007Fagundes et al ( , 2010, it has been shown that chronic methylphenidate exposure affected different activities in the brains of young and adult rats-while increasing mitochondrial respiratory chain enzymes in young rats' brains, it reduced them in adult brains. Andreazza et al (2007) has shown that methylphenidate led to central (in cells of the striatum and hippocampus tıssues of the brain) and peripheral (blood leukocytes) early DNA damage in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dysregulation of the expression of this gene has been implicated in some neuropsychiatric disorders such as bipolar disorder [55]. A previous study reported inhibition of mitochondrial respiratory chain complex III in the striatum as well as other brain regions of adult Wistar rats exposed to chronic (28 days) treatment of methylphenidate [56]. Downregulation of mitochondrial respiratory complex III (as well that of other complexes) has been viewed as a compensatory response in order to maintain energy homeostasis through enhancement of other metabolic systems [56].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported inhibition of mitochondrial respiratory chain complex III in the striatum as well as other brain regions of adult Wistar rats exposed to chronic (28 days) treatment of methylphenidate [56]. Downregulation of mitochondrial respiratory complex III (as well that of other complexes) has been viewed as a compensatory response in order to maintain energy homeostasis through enhancement of other metabolic systems [56]. Alternatively, it has been assumed to result from neurotoxic effects of methylphenidate via the generation of ROS [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fagundes et al [69] verified that complexes I, II, III and IV were inhibited in brain of adult rats by MPH acute administration. In addition, MPH increases central and peripheral indexes of early DNA damage in young and adult rats [70].…”
Section: Discussionmentioning
confidence: 96%